Learning style and foreign language learning: The effect of gender, handedness and direction of studies - Ανδρέου Ελένη; Ανδρέου Γεωργία; Βλάχος Φίλλιπος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF